2015
DOI: 10.1161/circulationaha.115.016270
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Persistent Flow Disturbances Accelerates Atherogenesis and Promotes Thin Cap Fibroatheroma Development in D374Y -PCSK9 Hypercholesterolemic Minipigs

Abstract: C oronary heart disease is projected to remain the worldwide leading cause of death until 2030.1 Coronary heart disease is a major cause of morbidity and reduced quality of life with enormous economic consequences.2,3 Atherosclerosis, a multifocal lipid-driven inflammatory process, is the principal underlying pathology in patients with coronary heart disease, which commonly presents clinically with symptoms secondary to luminal narrowing of an epicardial coronary artery or Background-Although disturbed flow is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 38 publications
5
45
0
1
Order By: Relevance
“…Because it does not account for flow reversal, it complements the OSI. This metric has recently been shown to correlate well with local regions of naturally occurring early plaques in the aorta of a rabbit model [36] and initiation of advanced plaques in pigs [1]. LSI and HSI quantify the degree of atherogenic low and high WSS, respectively, using a threshold determined by a non-diseased vessel (herein, we used the contralateral control artery within each mouse).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because it does not account for flow reversal, it complements the OSI. This metric has recently been shown to correlate well with local regions of naturally occurring early plaques in the aorta of a rabbit model [36] and initiation of advanced plaques in pigs [1]. LSI and HSI quantify the degree of atherogenic low and high WSS, respectively, using a threshold determined by a non-diseased vessel (herein, we used the contralateral control artery within each mouse).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these metrics quantify low and high WSS over a continuous scale compared with a binary approach used by previous studies [6,19]. These metrics have recently been introduced by us in a previous study where they showed good spatial overlap with advanced plaques, including thin cap fibroatheroma (TCFA), in hypercholesterolemic pigs [1]. Together with the results of this study, these metrics also demonstrate the advantage of scale invariance, where they can be used in animals of different sizes including humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, coronary reconstruction was performed using a methodology that did not include side branches which appear to affect ESS distribution 24. In addition, we assumed a steady and not a pulsatile flow profile; this may allow accurate estimation of the averaged ESS but it cannot assess the role of oscillating ESS on atherosclerotic evolution 25. Finally, the present study, which is the largest serial multimodality imaging study investigating the effect of ESS on plaque morphology, included only a subset of the patients recruited in the IBIS-4 study that included patients admitted with a myocardial infarction who received aggressive treatment with Rosuvastatin, a medication that influences plaque evolution; therefore, the reported results should be interpreted with caution as it is likely to not reflect plaque evolution in other populations.…”
Section: Resultsmentioning
confidence: 99%
“…A number of clinical and experimental studies using 3D imaging have shown that low shear stress is an important factor in the development of vulnerable plaques. 40,41 In the future, 3D models using 3D printing can provide more accurate models for the study of pathophysiology and assist in evaluating optimal interventional techniques for a patient. 42 …”
Section: Emergence Of Intravascular Imaging and Physiology Assessmentmentioning
confidence: 99%